Estudio de factibilidad, aplicando la metodología de Canvas, para proponer el plan de negocios del turismo ecológico y de aventura de la comunidad Cofán Dureno, en la parroquia Dureno del cantón Lago Agrio - Loaiza Blacio, María del Carmen (2016)
The study was conducted in the Province of Sucumbíos, aimed to prepare the feasibility study, applying the methodology of KEDS, to propose the business plan ecotourism and adventure of the Cofán Dureno community in Dureno Parish of Canton Lago Agrio, considered attractive by its population, but not recognized in tourism and legalization process according to their activity, why it was raised Titling this work; He proceeded to make a diagnosis, together with a feasibility study, which was able to determine current industry conditions, as; climatic, economic, tourist, social and productive aspects through the techniques of observation and interpretation, using survey instruments, and records information gathering, generating identify demand and tourism to which this proposal addressed, gaining knowledge tourism and socio-economic impact was strong. The proposal established guidelines for a community responsible and sustainable tourism, united not only a consequence of applying the business plan using the methodology of KEDS ecotourism and adventure of the Cofán Dureno community in Dureno Parish of Canton Lake Sour; gathering information was achieved by the situational analysis, also the feasibility study was carried out to obtain the viability of the project and thus develop the business plan, tourism activities was developed in played in ecological and tourism venture Cofán Community Dureno.